Uganda : Technical Assistance Report-Managing and Preventing Expenditure Arrears. (IMF Staff Country Reports; Country Report ;, 2017)
This Technical Assistance Report discusses recommendation for managing and preventing expenditure arrears in Uganda. There is need to reconcile the verified stock of arrears with those reported in the annual financial statements. The verification for Budgetary Central Government must be completed, and mechanisms for regular reporting and verification of arrears by local government and the broader public sector must be established. It is also recommended to develop and publish an arrears clearance strategy including prioritization criteria, liquidation policy and institutional responsibility for monitoring and clearance of arrears.